Menyikapi Toxic Masculinity melalui Fenomenologi Merleau Ponty - Riko Silaen; Albertus Daniel Simanungkalit; Erastus Sabdono; Stephanie Erastus; Jemy Saleky Combi (Sekolah Tinggi Teologi Baptis, Jakarta, 2024)
Toxic Masculinity is a problem that is rooted in false rationalization. This rationalization becomes crystallization since the masses agree on it together. As a result, it becomes an objective view and lifestyle. The Apostle Paul proclaimed equality in this regard, of course, equality when living in Jesus Christ. This is the foundation for those of us who believe in Him. However, this equality must be felt and experienced. This research uses a library research method with a qualitative approach. Merleau Ponty's phenomenology invites you to feel that feeling